Dual-Hemisphere Transcranial Direct Current Stimulation on Parietal Operculum Does Not Affect the Programming of Intra-limb Anticipatory Postural Adjustments - Esposti, Roberto; Marchese, Silvia M.; Farinelli, Veronica; Bolzoni, Francesco; Cavallari, Paolo (Frontiers in Physiology, 2021)
Evidence shows that the postural and focal components within the voluntary motor command are functionally unique. In 2015, we reported that the supplementary motor area processes Anticipatory Postural Adjustments (APAs) separately from the command to focal muscles, so we are still searching for a hierarchically higher area able to process both components. Among these, the parietal operculum (PO) seemed to be a good candidate, as it is a hub integrating both sensory and motor streams. However, in 2019, we reported that transcranial Direct Current Stimulation (tDCS), applied with an active electrode on the PO contralateral to the moving segment vs. a larger reference electrode on the opposite forehead, did not affect intra-limb APAs associated to brisk flexions of the index-finger. Nevertheless, literature reports that two active electrodes of opposite polarities, one on each PO (dual-hemisphere, dh-tDCS), elicit stronger effects than the “active vs. reference” arrangement. Thus, in the present study, the same intra-limb APAs were recorded before, during and after dh-tDCS on PO. Twenty right-handed subjects were tested, ten for each polarity: anode on the left vs. cathode on the right, and vice versa. Again, dh-tDCS was ineffective on APA amplitude and timing, as well as on prime mover recruitment and index-finger kinematics. These results confirm the conclusion that PO does not take part in intra-limb APA control. Therefore, our search for an area in which the motor command to prime mover and postural muscles are still processed together will have to address other structures.